2004
DOI: 10.1158/0008-5472.can-03-2707
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib as a Potential Treatment for Prostate Cancer

Abstract: Androgen ablation and chemotherapy provide effective palliation for most patients with advanced prostate cancer, but eventually progressing androgen-independent prostate cancer threatens the lives of patients usually within a few years, mandating improvement in therapy. Proteasome inhibition has been proposed as a therapy target for the treatment of solid and hematological malignancies. The proteasome is a ubiquitous enzyme complex that is a hub for the regulation of many intracellular regulatory pathways; bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 90 publications
(82 reference statements)
2
105
0
3
Order By: Relevance
“…Also, dexamethasone, a glucocorticoid used commonly for prostate cancer treatment, disrupts the NF-kB-IL-6 pathway and this is thought to mediate the antitumour effect (Nishimura et al, 2001). Finally, recent evidence in a phase I clinical trial has suggested that the proteasome inhibitor bortezomib has activity against human prostate cancer and reduces the expression of serum IL-6 and PSA levels in some patients (Papandreou and Logothetis, 2004). This is relevant here since the degradation of the inhibitor of NF-kB, IkB, is dependent on the ubiquitin -proteasome pathway, and proteasome inhibition results in inhibition of NF-kB (Elliott and Ross, 2001;Adams, 2004;Papandreou and Logothetis, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Also, dexamethasone, a glucocorticoid used commonly for prostate cancer treatment, disrupts the NF-kB-IL-6 pathway and this is thought to mediate the antitumour effect (Nishimura et al, 2001). Finally, recent evidence in a phase I clinical trial has suggested that the proteasome inhibitor bortezomib has activity against human prostate cancer and reduces the expression of serum IL-6 and PSA levels in some patients (Papandreou and Logothetis, 2004). This is relevant here since the degradation of the inhibitor of NF-kB, IkB, is dependent on the ubiquitin -proteasome pathway, and proteasome inhibition results in inhibition of NF-kB (Elliott and Ross, 2001;Adams, 2004;Papandreou and Logothetis, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This lower risk group may benefit from the addition of less toxic systemic agents to achieve longterm control and may be considered for randomized Phase II trials examining the impact of promising novel systemic therapies in addition to ADT on the time to PSA failure. Some of these novel agents include Thalidomide, 20,21 endothelin receptor A antagonists, 22,23 proteasome inhibitors, 24,25 and vaccines. [26][27][28] The agents that show the longest prolongation in time to PSA failure with minimal toxicity then may be considered for study in future Phase III trials.…”
Section: Discussionmentioning
confidence: 99%
“…Akt causes the NFkB binding protein, IkB, to release NFkB, which then translocates to the nucleus where it transcribes multiple genes involved with proliferation, inflammation, cell adhesion, stress response and antiapoptosis. 15 NFkB also increases expression of matrix metalloproteinases, which are frequently elevated in CaP specimens and may play a role in promoting invasion and metastasis.…”
Section: Inhibition Of Akt Pathwaysmentioning
confidence: 99%